Serpentine : The Evolution and Ecology of a Model System - Rajakaruna, Nishanta, 1969-; Harrison, Susan (Susan Patricia) (Book collections on Project MUSE., 2011)
Serpentine soils have long fascinated biologists for the specialized floras they support and the challenges they pose to plant survival and growth. This volume focuses on what scientists have learned about major questions in earth history evolution, ecology, conservation, and restoration from the study of serpentine areas, especially in California. Results from molecular studies offer insight into evolutionary patterns, while new ecological research examines both species and communities. Serpentine highlights research whose breadth provides context and fresh insights into the evolution and ecology of stressful environments.